2013
DOI: 10.1371/journal.pone.0057724
|View full text |Cite
|
Sign up to set email alerts
|

Met Is the Most Frequently Amplified Gene in Endometriosis-Associated Ovarian Clear Cell Adenocarcinoma and Correlates with Worsened Prognosis

Abstract: Clear cell adenocarcinoma of the ovary (OCC) is a chemo-resistant tumor with a relatively poor prognosis and is frequently associated with endometriosis. Although it is assumed that oxidative stress plays some role in the malignant transformation of this tumor, the characteristic molecular events leading to carcinogenesis remain unknown. In this study, an array-based comparative genomic hybridization (CGH) analysis revealed Met gene amplification in 4/13 OCC primary tumors and 2/8 OCC cell lines. Amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 39 publications
2
50
1
3
Order By: Relevance
“…PIK3CA mutation with gain of function has been suggested to occur in 33-40% of OCCC and 12-20% of EnOC [18]. Furthermore, in a previous study AKT2 amplification was observed in 14% of OCCC cases [19]. In addition to these genetic alterations, the loss of PTEN expression has been detected in 40% of OCCC [20].…”
Section: Alteration Of the Pi3k/akt/mtor Pathway In Ovarian Cancermentioning
confidence: 90%
“…PIK3CA mutation with gain of function has been suggested to occur in 33-40% of OCCC and 12-20% of EnOC [18]. Furthermore, in a previous study AKT2 amplification was observed in 14% of OCCC cases [19]. In addition to these genetic alterations, the loss of PTEN expression has been detected in 40% of OCCC [20].…”
Section: Alteration Of the Pi3k/akt/mtor Pathway In Ovarian Cancermentioning
confidence: 90%
“…Our FISH analysis is highly sensitive because we probed BAC DNA containing full-length HCMV genome, and in our previous study, we could readily detect two copies of the human genome in a cell using the same method. 24 Earlier studies reporting positive signals of HCMV DNA and RNA in the glioblastoma cells by in situ hybridization utilized antibody-mediated enhancement of the primary signals, 1,2 which may have resulted in augmentation of nonspecific bindings of the probes, leading to misinterpretation of the signals. Furthermore, our LC/MS/MS analysis revealed that proteins extracted from the positive bands detected in immunoblotting using IE1 and pp28 antibodies were non-viral human proteins such as HSA and MBP, suggesting previously unknown cross-reactivity of these antibodies and also the unreliability of not only positive immunoblot bands but also immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
“…23 Fluorescence In Situ Hybridization HCMV BAC DNA was labeled with SpectrumOrange using a Nick Translation Kit (Abbott Molecular, Abbott Park, IL, USA) according to the manufacturer's recommendation and FISH analysis for HCMV genome detection was performed as described previously. 24 …”
Section: Liquid Chromatography-tandem Mass Spectrometry (Lc/ms/ms) Anmentioning
confidence: 99%
“…20,21 Compared with serous adenocarcinoma, clear cell adenocarcinoma is resistant to standard platinum-based chemotherapy; 22 thus, survival rates in patients with advanced stages of ovarian clear cell adenocarcinoma are poor. Therefore, it is important to distinguish clear cell adenocarcinoma from other histological subtypes in ovarian cancer.…”
mentioning
confidence: 99%